2009
DOI: 10.1111/j.1365-2044.2009.06159.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of haemostasis in liver transplantation: comparison of laboratory based and point of care tests

Abstract: SummaryDuring orthotopic liver transplanatation haemostasis is often disturbed and coagulation monitoring is mandatory. We compared the results obtained by whole blood prothrombin time and activated partial thromboplastin time assays (Hemochron Ò ) and thrombelastometry (ROTEM Ò 05) with laboratory coagulation assays (prothrombin time, activated partial prothrombin time, fibrinogen, and platelet count) in samples obtained during orthotopic liver transplantations. Determination of prothrombin time and activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 15 publications
(19 reference statements)
5
38
0
1
Order By: Relevance
“…Clinically and during surgery many patients with high INR do not bleed even when no blood transfusion products are infused. Herbstreit et al demonstrated also that clot formation time of thrombelastometry and the standard coagulation tests as PT and aPTT showed poor correlation similar to our study [14]. The poor presence of blood cellular structures as endothelial cells and platelets during most of the standard conventional tests could explain the lack of a significant correlation between these tests and the ROTEM parameters due to the difference in methodology of measurement.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Clinically and during surgery many patients with high INR do not bleed even when no blood transfusion products are infused. Herbstreit et al demonstrated also that clot formation time of thrombelastometry and the standard coagulation tests as PT and aPTT showed poor correlation similar to our study [14]. The poor presence of blood cellular structures as endothelial cells and platelets during most of the standard conventional tests could explain the lack of a significant correlation between these tests and the ROTEM parameters due to the difference in methodology of measurement.…”
Section: Discussionsupporting
confidence: 77%
“…12Several studies with particular interest in hepatic patients subjected to liver surgery were able to present an activation of the coagulation cascade reaching some times to a hypercoagulable state due to the sustained up regulation of the coagulation process itself [13]. Standard coagulation tests in these situations could give false impression of a state of hypocoagulability when instead the patient would indeed need prophylactic anticoagulation measures to manage the undiagnosed hypercoagulable status [2][3][4]14].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, samples taken during the earlier phases of the transplantation support the findings of Herbstreit et al who found a strong positive correlation between pocINR and laboratory PT estimations (r = 0.91) using the same POC device in liver transplantation. 15 The pocINR performed well at predicting the direction of change of labINR between the three critical phases of liver transplantation (Fig. 3).…”
Section: Discussionmentioning
confidence: 82%
“…[15][16][17] As the trigger for intraoperative transfusion is usually at a lower INR level, this outcome is unlikely to be of relevance in a perioperative liver transplant population. Our study did not replicate this finding; however, relatively few (20%) INR readings in the labINR and pocINR groups were[2.5.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the blood coagulation test technology and the discovery of coagulation cascade have contributed to the rapid development of coagulation time testing. The main test methods include prothrombin time (PT), activated partial thromboplastin time (APTT), thromboplastin time (TT), and activation of coagulation time (ACT) [3] [4]. In order to obtain a comprehensive and effective evaluation of the blood coagulation and fibrinolysis function, it is far from enough to rely on routine tests and regular indicators, especially in a large surgical procedure such as a cardiac surgery and a liver transplant.…”
Section: Introductionmentioning
confidence: 99%